Understanding Philippine History Education in the Age of Disinformation: A Phenomenological Exploration - Amando F. Grata; Raquel F. Llaneta (Ilmu Inovasi Nusantara, 2024)
In Philippine history education, the growing influence of digital media has shifted students' learning preferences, offering both opportunities and challenges. The widespread use of social media platforms like Facebook, YouTube, and TikTok has affected how students access and engage with historical content. A key challenge is that social media, with its easily digestible information, impacts students' attention spans and trust in traditional versus digital sources. This shift underscores the importance of integrating multimedia tools into history education while maintaining rigorous academic standards. This study examines how students' inclination toward social media influences their engagement with historical content and trust in information sources. Using a phenomenological approach, data were collected through in-depth interviews with students from diverse educational backgrounds. The analysis highlights the growing reliance on visual and auditory learning methods, reflecting the